Inter-observer and intra-observer reliability of the myopic traction maculopathy staging system. Issue 3 (May 2022) - Frisina, Rino; Besozzi, Gianluca; Finzi, Alessandro; Pinackatt, Sajish Joseph; Palmieri, Michele; Parolini, Barbara
Aim: The aim of this study is to evaluate the inter-observer and intra-observer agreement of the myopic traction maculopathy (MTM) staging system (MSS). Methods: The agreement test for MSS was based on the evaluation of 104 optical coherence tomography (OCT) scans from 104 myopic eyes. According to the MSS, six observers were asked to identify, in each image, one among four retinal patterns and one among three foveal patterns of MTM, the presence of an outer lamellar macular hole (OLMH) and an epiretinal membrane (ERM). Each observer repeated the agreement test after a 60 days interval. Results: Inter-observer reliability: the agreement of the test for the retina pattern was substantial (0.724), for the fovea pattern was 0.821, for the OLMH was 0.656, and for the ERM was 0.463. When all the criteria are included in the validation test the agreement was 0.657. Regarding the weighted statistics (Gwet's AC2, 95% CI), the validation test was statistically significant both when the variables were considered one by one, with an excellent agreement, respectively for the retina pattern (0.955) and the fovea pattern (0.963) and when all the variables were included in the tests (0.930). Intra-observer repeatability: all observers rerun the test after 2 months with a statistically significant percentage of confirmation of the previous test. Conclusion: The MSS offers in one Table information on diagnosis, natural history, function, prognosis, and management of MTM. The MSS is user-friendly and highly reproducible.